Intervention and treatment for substance use disorder: An overview in Malaysia - Norzihan Ayub; Norafifah Bali (Herald Scholarly Open Access, 2022)
Substance Use Disorder (SUD) are patterns of maladaptive use of psychoactive drugs that lead to significant levels of impaired functioning or personal distress. SUD often result in not only serious harm to the health of the individuals, but also enormous financial and social consequences that go beyond the health care system such as loss of economic productivity due to withdrawal from the workplace and increased rates of crime, injury, disability and death. Individuals who experience a Substance Use Disorder (SUD) may also experience a dual diagnosis or co-occurring mental disorder such as anxiety, psychosis, depression and others. A dual diagnosis presents a challenging problem to mental health workers and service planners as Substance Use Disorders (SUD) occurring together with mental health disorders represent a major health problem. SUD is also a heavy burden for the government because it needs a lot of enforcement from the authorities and drains available health care resources. Moreover, the intervention and treatment of SUD is a complex, multidimensional, and long-term endeavor that often requires specialized care tailored to the substance and the severity of the pattern of use. Therefore this paper aims to discuss an overview of SUD and it also cover the contributory factors of SUD and intervention or treatment modalities available for its management in Malaysia.